Heating Calculation for Multi-Layer Bodies - R. I. Yesman (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a mathematical model and numerical solution of a problem in 2D-heating of multi-layer bodies. работе приведена математическая модель и численное решение задачи в двумерной постановке нагрева  2D –heating многослойных тел. Displacement of phase transformation front along layer section is taken into account in  the paper.The developed mathematical model is applied for calculation of temperature fields in the process of obtaining multi-layer products with special properties.Such products with the given operating characteristics can be applied in new innovation technologies of power and machine building engineering.